A conceptual framework of clinical nursing care in intensive care - Rafael Celestino da Silva; Márcia de Assunção Ferreira; Thémistoklis Apostolidis; Marcos Antônio Gomes Brandão (Universidade de São Paulo, 2015)
Objective: to propose a conceptual framework for clinical nursing care in intensive care.Method: descriptive and qualitative field research, carried out with 21 nurses from an intensive care unit of a federal public hospital. We conducted semi-structured interviews and thematic and lexical content analysis, supported by Alceste software.Results: the characteristics of clinical intensive care emerge from the specialized knowledge of the interaction, the work context, types of patients and nurses characteristic of the intensive care and care frameworks.Conclusion: the conceptual framework of the clinic's intensive care articulates elements characteristic of the dynamics of this scenario: objective elements regarding technology and attention to equipment and subjective elements related to human interaction, specific of nursing care, countering criticism based on dehumanization.